Discover a new species of genus Bombus Latreille, 1802 (Hymenoptera, Apidae) from Vietnam - Hue, Le Xuan (Academia Journal of Biology, 2012)
In this paper we depict a species of genus Bombus as new species for Science. Bombus lagubrunus Le, sp. nov. Female: Head and Face not elongate. Head and front with short black pubescence, black clypeus. The apex of scape and second segment of antennae with light brown. Labrum, mandibles and remain segments of antennae dark black. Black eyes. Pronotum and mesonotum with yellow pubescence. In the middle of mesonotum without pubescence and transverse band of black pubescence. Mesepisternum, Scutellum and Metanotum with short yellow hair. Wings hyaline, with brow veins and fuscous cloud on the lateral margin of fore wing. Legs black, tibia and tarsus with fusco - yellow to dark brow. Tergits of abdomen with brow pubescence. Leng of body about 25 mm. Male unknown. Holotype: 1 female Son La (Thuan Chau, Co Ma) 9/6/2008. Paratyp: 1 female (as above mentioned). This new species differ from Bombus haemorrhoidalis Smith, 1852 by head and face not elongate, brow pubescence on tergites of abdomen; Wing hyaline, with brow veins and fuscous cloud on the lateral margin of fore wing.